Mapping technology roadblocks and opportunities in the transportation revolution. Issue 4 (16th July 2019) - Blitz, Amy; Kazi, Khurram
Abstract : Purpose: This paper aims to set out a vision of the advent of autonomous electric vehicles (AEV), piloted by artificial intelligence and serviced by other "intelligent" machines, a scenario that poses vast implications for business strategy in many industries. Design/methodology/approach: Given the speed with which business leaders today must assess and react to the business risks and opportunities engendered by breakthrough technological change, their plans to navigate an autonomous electric vehicle-based transportation future can benefit from a scenario map to the roadblocks and the richest prospects. Findings: Self-driving electric cars and trucks, which are expected to transform the transportation landscape over the next decade. A smart charging grid is a critical technology development. Practical implications: Business opportunities to transform ground transport in areas such as operations and supply chain management are significant as well, particularly with unsupervised AEVs, which could slash labor costs and transport times. Social implications: AEVs are expected to free up more than 30 billion hours per year in the U.S. alone currently spent driving, sitting in traffic or searching for a parking space. Originality/value: Offers a look at the technology evolution needed for the AEV transportation revolution.